Prevalence and risk factors of stroke-related sarcopenia at the subacute stage: A case control study - Yao, Ruihong; Yao, Liqing; Rao, Amin; Ou, Jibing; Wang, Wenli; Hou, Qinzhi; Xu, Chunyan; Gao, Bu-Lang (Frontiers in Neurology, 2022)
Purpose: To investigate the prevalence and risk factors of stroke-related sarcopenia (SRS) in hospitalized patients receiving rehabilitation treatment. Methods: 259 stroke patients satisfied the inclusion and exclusion criteria were consecutively recruited between June 2020 and July 2022. The epidemiologic data, history, clinical data and measured data of the skeletal muscle index were collected. The patients were divided into the sarcopenia and non-sarcopenia group for comparison and analysis with the univariate and multivariate analysis. Results: SRS was presented in 121 (46.7%) patients with a mean age of 59.6 ±9.7 years, including 42 females and 79 males. Multivariate logistic regression analysis revealed the following parameters to be significant (P<0.05) risk factors for SRS: college degree or above (OR 2.1, 95% CI 1.1-4.1), ICU stay (OR 1.7, 95% CI 1.06-2.8), pneumonia (OR 1.9, 9% CI 1.1-3.6), walking ability (OR 2.6, 95% CI 1.5-4.6), cognitive impairment (OR 1.8, 95% 1.1-2.9), aphasia (OR 2.1, 95% CI 1.2-3.5), nasogastric feeding (OR 3.7, 95% 1.9-7.3), age (OR 1.04, 95% CI 1.0-1.1), and creatine kinase (OR 1.1, 95% CI 0.9-1.2).whereas the following parameters played a protective role for SRS: weight (OR 0.88, 95% CI 0.85-0.92), albumin (OR, 0.89, 95% CI 0.82-0.97), RAG (OR 0.12, 95% CI 0.04-0.4), creatinine (OR 0.994, 95% CI 0.989-1.0), uric acid (OR 0.996, 95% CI 0.993-0.998), red blood cells (OR 0.463, 95% CI 0.3-0.7), hemoglobin (OR 0.968, 95% CI 0.954-0.982), prealbumin (OR 0.99, 95% CI 0.986-0.994), and iron (OR 0.93, 95% CI 0.89-0.98). Conclusions: Older age, light weight, severer clinical conditions, cognitive impairment, and significantly decreased levels of albumin, RAG, creatinine, uric acid, red blood cell count, hemoglobin, prealbumin, iron, and creatine kinase are more significantly present in patients with SRS compared with those without SRS.